Hydrochemical Characteristics and Control Factors of Strontium Enrichment of Groundwater in the Eastern Sanjiang Plain, China - Jingjie Li; Mingguo Wang; Tao Yang; Sheng Lian; Huaisheng Zhang; Chao Bian; Xuqing Wang; Shixiong Tian (Journal of Chemistry)
Strontium (Sr) is one of the essential trace elements in the human body, which has important biological significance for human physiological function. In this paper, 41 groundwater samples collected from Shengli Farm in the eastern Sanjiang Plain were used to study the hydrochemical characteristics of Sr2+ enrichment and its control factors by correlation analysis, principal component analysis, and Gibbs model, which is helpful to guide the rational development and utilization of local groundwater resources and ecological environment protection.The findings indicate that the groundwater exists in a reducing environment characterized by acidity and low salinity, with predominant cations being Ca2+ and Mg2+, and predominant anions being HCO3−. The predominant hydrochemical type is HCO3-Ca·Mg, secondly by SO4·Cl-Ca·Mg type. Principal component analysis identifies three primary elements influencing the evolution of groundwater quality. The weathering and dissolution of silicate and carbonate rocks are the primary forces influencing the chemical composition of water, secondly by the dissolution of evaporites. Groundwater with a Sr content over 0.40 mg/L constituted 7.32% of the total samples. The siliceous rocks and basalts present in this region supply the foundational material for Sr2+ enrichment. Sr2+ is correlated and coenriched with Ca2+ and Mg2+, and the liberation of Sr2+ from adjacent rock during cation exchange is one of the sources of Sr2+ in groundwater. Regular agricultural and livestock practices are the primary contributors to the elevation of SO42- levels in adjacent groundwater, as well as the enhancement of Sr2+ concentrations.